Understanding the drivers of modern contraceptive use trend change and inequalities among sexually active women in Lesotho: A decomposition analysis (2004–2023) - Million Phiri; Mapitso Lebuso; Nthatisi Leseba; Talent Tapera; Joseph Kazibwe; Nebechukwu Henry Ugwu; Garikayi Bernard Chemhaka (PLoS ONE, 2026)
Background Improving utilization of contraceptive methods serves as a powerful catalyst for advancing women’s education, health, and personal autonomy. Many countries have pledged to enhance contraceptive availability as part of their commitment to the Sustainable Development Goals (SDGs), specifically under indicator 3.7.1. This study sought to understand the drivers of modern contraceptive use trend and inequalities among sexually active women of reproductive ages in Lesotho during the period 2004–2023. Methods The study used four rounds of Lesotho demographic and health survey datasets for the years 2004, 2009, 2014 and 2023. A total sample of 22,325 sexually active women of reproductive ages 15–49 years was used in the analysis. Blinder-Oaxaca decomposition technique was used to analyse drivers of trend change in modern contraceptive while the concentration curves and indices were used to assess the levels of inequality. All analyses were conducted in Stata software version 17 and weighted to account for complex sampling techniques in demographic and health surveys. Results The prevalence of modern contraceptive use among sexually active women increased significantly from 36.1% (95% CI: 34.2, 37.9) to 62.7% (95% CI: 61.1, 64.2) during the period 2004–2023. Overall, about 10% of the trend increase in modern contraceptive use was attributable to changes in the compositional characteristics of women. On the other hand, 90% of the trend increase was due to contraceptive behaviour change among sexually active women. Changes in the proportion of women with tertiary education (22.41%) emerged as the major contributor to trend increase in modern contraceptive use. The concentration curves showed that utilization of modern contraceptive methods was profoundly higher among the wealthy than the poor in the first three rounds of the surveys and disappeared in the last round (2023). This pro-rich inequality was persisted throughout the study period except for 2023 where it disappeared. Erreygers concentration Index (EI) values were 0.2360 in 2004, 0.1606 in 2009, 0.0473 in 2014 and −0.0164 in 2023. Conclusion The observed reduction in inequality in modern contraceptive use in Lesotho from 2004 to 2023 reflects meaningful progress in women’s reproductive autonomy. This could be explained by improvements in education, health service access, empowerment, and social change. Sustaining these gains will depend on continued investments in the health system, educational opportunities, and community-engaged approaches that are culturally sensitive to respond to the contraceptive barriers and shifting demographic realities.